Upaya Meningkatkan Kemampuan Mengenal Angka 1-10 Melalui Media Bermain Kartu Angka Pada Anak Usia Dini - Desty Survia; Desmiati Mulanirum (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The aim of the research is to improve the ability to number 1–10 through the method of playing number cards in group A children at Teratai IX Early Childhood Education. The research was carried out through classroom actions in two cycles on 13 students in group A. Research results: In cycle 1 action, the ability to number numbers 1-10 reached an average of 4 children (81%), the ability to number numbers 4-6 reached an average of 3 children (41%), and the ability to number 1-3 reaches an average of 6 children (21%). In cycle 2 of action, the ability to say numbers 1-10 reached an average of 7 children (100%), and the ability to say numbers 4-6 reached an average of 5 children (60%). And the ability to number 1-3 reaches 1 child (40%). Effective steps in improving children's numeration skills: the teacher changes learning techniques into groups, gives rewards in the form of star marks, the size of the numbers on the cards, and equips with a Children's Worksheet, the number of number cards 1-10 is made according to the child's needs.